Development of Journalism Development Strategies in The Digital Era at Darul Mukhlasin High School - Islam, Izul; Ishaq, Maulana (JERIT: Journal of Educational Research and Innovation Technology, 2024)
The development of the digital world has brought significant changes in various aspects of education, including school journalism. Journalism in schools is no longer limited to print activities or wall magazines but has transformed into a more interactive and dynamic digital platform. High School Darul Mukhlasin is one institution that realises the need to adapt to this change. High School Darul Mukhlasin realises the importance of adapting to technology to improve students' literacy, creativity, and communication skills through digital journalism. This article discusses the strategy of developing digital journalism at High School Darul Mukhlasin, the challenges faced such as limited technological infrastructure, lack of digital skills, and low student interest in journalism, and the solutions implemented to overcome these problems. With a descriptive qualitative approach, the results show great opportunities in improving students' skills through training, creative content development, and collaboration with professional media.